Simplify (1+iroot3)^9 + (1-iroot3)^9 in x+iy form

1 answer

1 + √3 i = 2 cis π/3
so, (1 + √3 i)^9 = 2^9 cis (9 * π/3) 512 cis 3π = -512
Now do the other.
Similar Questions
    1. answers icon 4 answers
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
    1. answers icon 1 answer
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
more similar questions